Analisis Stabilitas Lereng dan Penanganan Longsor dengan Dinding Penahan di Palaran, Samarinda. - Muhammad Hafidz; Revia Oktaviani; Tommy Trides; Albertus Juvensius; Agus winarno (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Landslides or commonly called landslides are a disaster that often hits areas with tropical climates. The damage caused by landslides is most dominantly structural damage such as damaged road sections that are cut off. At the research location, there was a landslide that resulted in the obstruction of the road flow which was originally two lanes to one lane, it is feared that landslides will occur again, so one of the landslide prevention techniques is to use retaining walls. Based on this, this study is deemed necessary to determine the slope safety factor and to determine the safety of the slope after using retaining walls. The purpose of this study was to determine the level of slope safety without being given a load, the level of slope safety after being given a load of 25 Kpa and the level of slope safety after being given a load of 25 kpa and the addition of a retaining wall on the research slope using a Retaining Wall. In this study using the Finite Element Method in the calculation to find the level of safety of a slope, the researcher used the help of Plaxis 2D V20 Software, and the results of the calculation obtained a slope safety factor of 1.31, after being given a load of 25 kpa the slope safety factor was 1.14 and after being given a retaining wall the slope safety factor increased to 2.46.